2005
DOI: 10.1111/j.1439-0523.2004.01063.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and inheritance studies of partial resistance in the Brassica napus–Albugo candida host‐pathogen interaction

Abstract: Traditional and doubled haploid (DH) genotypes of oilseed Brassica spp. resistant, partially resistant, moderately susceptible, and susceptible to Albugo candida were compared for phenotypic development of host-pathogen interaction and histology of host-pathogen interaction. The partially resistant genotype showed pinhead-size pustules, mainly on the upper surface of cotyledonary leaves. Relatively less mycelium was observed in the partially resistant genotype compared with the susceptible genotype. In resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Under controlled conditions, inoculation with three different races of A. candida on F2 population of crosses from resistant × resistant revealed that the resistant genes may be located on the same locus or on different loci. Partial resistance in B. napus to A. candida was controlled by a single recessive gene designated as wpr with a variable expression (Bansal et al 2005). White rust resistance in B. juncea (Somers et al 2002, Manjunath et al 2007) and avirulence in race AC 2 of A. candida to B. rapa cv.…”
Section: Host Plant Resistancementioning
confidence: 99%
“…Under controlled conditions, inoculation with three different races of A. candida on F2 population of crosses from resistant × resistant revealed that the resistant genes may be located on the same locus or on different loci. Partial resistance in B. napus to A. candida was controlled by a single recessive gene designated as wpr with a variable expression (Bansal et al 2005). White rust resistance in B. juncea (Somers et al 2002, Manjunath et al 2007) and avirulence in race AC 2 of A. candida to B. rapa cv.…”
Section: Host Plant Resistancementioning
confidence: 99%